Scientific literature analysis on sustainability with the implication of open innovation (2020)
Studies related to sustainability have been performed extensively around the world to evaluate the environmental, economic, and social impact of practices that meet the current and future needs of society. Based on the Scopus database, this study presents a bibliometric analysis for the long, medium, and short term to represent the characteristics of publications related to sustainability, identify research trends and thematic areas with a promising future in research. The analysis covers the following topics: general statistical description, most addressed thematic areas in sustainability, the geographical distribution of sustainability publications, and most influential and cited journals, authors, and articles. The results show sustainability prevails in areas like Engineering, Energy, Environmental Science, and Business, Management, and Accounting, and the publication rate in this field has increased exponentially in the last 10 years. This study also shows that the most productive journals in sustainability research are Sustainability Switzerland and Journal of Cleaner Production, focusing on interdisciplinary and transdisciplinary topics. Likewise, the critical issues of sustainability research are related to sustainable development, humans, environmental sustainability, climate change, decision-making, and environmental impact. As sustainability with open innovation represents a topic with an increasing number of publications, future research can be oriented toward this topic. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.